2017
DOI: 10.1177/0004867417741981
|View full text |Cite
|
Sign up to set email alerts
|

A profile of social, separation and generalized anxiety disorders in an Australian nationally representative sample of children and adolescents: Prevalence, comorbidity and correlates

Abstract: Social, separation and generalized anxiety disorders in young people are relatively common and impairing, with a high level of comorbidity. There are both commonalities and differences in socio-environmental correlates. The majority of anxious youth received some form of professional assistance, although the rate was lower among children compared to adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
25
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 43 publications
9
25
2
Order By: Relevance
“…Temperamentally inhibited children do tend to experience a variety of daily-life circumstances to be stressful in comparison to their uninhibited peers. Also consistent with other international studies, we found that more mid-childhood life-stressors was associated with more child internalizing problems [28][29][30][31][32][33][34][35]37]. It is clear that temperamentally inhibited children facing general life-stressors are at some risk for developing internalizing problems.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Temperamentally inhibited children do tend to experience a variety of daily-life circumstances to be stressful in comparison to their uninhibited peers. Also consistent with other international studies, we found that more mid-childhood life-stressors was associated with more child internalizing problems [28][29][30][31][32][33][34][35]37]. It is clear that temperamentally inhibited children facing general life-stressors are at some risk for developing internalizing problems.…”
Section: Discussionsupporting
confidence: 90%
“…Research suggests that general life-stressors can contribute to youth internalizing problems [29][30][31]. Children with anxiety disorders tend to experience more stressful life events prior to onset of the disorder and perceive these events as more impactful compared to their non-anxious counterparts [28,29,[32][33][34][35]. Lifestressors are also associated with youth depression [36][37][38][39][40][41].…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, they may reflect a risk of social anxiety in children as a response to factors associated with relatively low SES. As few studies have compared socio‐economic status across different childhood anxiety disorders any conclusions must remain tentative, particularly in the light of recent Australian data that did not find significant differences in social and environmental factors, such as family income, between different anxiety disorders (Spence, Zubrick, & Lawrence, ). Critically, responses from parents were solely based on self‐report measures and formal diagnoses were not made.…”
Section: Discussionmentioning
confidence: 99%
“…We have not combined with other recent prevalence studies as data are not comparable due to different time periods covered (e.g. Spence, Zubrick, & Lawrence, ).…”
Section: Introductionmentioning
confidence: 99%